2020
DOI: 10.3390/atmos11101125
|View full text |Cite
|
Sign up to set email alerts
|

Kriging Interpolation in Modelling Tropospheric Wet Delay

Abstract: This contribution implements the Kriging interpolation in predicting the tropospheric wet delays using global navigation satellite system networks. The predicted tropospheric delays can be used in strengthening the precise point positioning models and numerical weather prediction models. In order to evaluate the performances of the Kriging interpolation, a sparse network with 8 stations and a dense network with 19 stations from continuously operating reference stations (CORS) of the Netherlands are selected as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This is because the weights of the Kriging interpolation depend upon the distances and time variation between the unknown points and all available measurements, as well as the covariance reflected in the semivariogram. It is well known that a neutral atmosphere is stable over a small region, as supported by related studies [18,31]. Therefore, the Kriging interpolation is suitable for generating the tropospheric delay corrections because the neutral atmosphere exhibits a noticeable spatial autocorrelation.…”
Section: Ppp-rtk Model and Tropospheric Correctionsmentioning
confidence: 83%
“…This is because the weights of the Kriging interpolation depend upon the distances and time variation between the unknown points and all available measurements, as well as the covariance reflected in the semivariogram. It is well known that a neutral atmosphere is stable over a small region, as supported by related studies [18,31]. Therefore, the Kriging interpolation is suitable for generating the tropospheric delay corrections because the neutral atmosphere exhibits a noticeable spatial autocorrelation.…”
Section: Ppp-rtk Model and Tropospheric Correctionsmentioning
confidence: 83%
“…These estimations can then be interpolated to the position of a user station within the network, allowing for the correction of the user measurements. A large number of field tests in previous studies have well tested and demonstrated this network-RTK approach [ 25 , 58 ].…”
Section: Functional Modelmentioning
confidence: 99%
“…Moreover, accurate predictions of the rover’s ZTD outside the network are mainly determined by the distance to a nearby reference station and are thus unaffected by the number of reference stations. In conclusion, Kriging interpolation depends on the distances between unknown points, all available measurements, and the covariance shown in the semivariogram [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, researchers have proposed many methods to deal with tropospheric delay, of which the following two are frequently applied in PPP: model correction method and parameter estimation method. The model correction method has been previously used to establish a mathematical model to correct tropospheric delay based on the physical characteristics of the troposphere and the functional relationship between meteorological parameters that affect its characteristics and tropospheric delay [10,11]. The model correction method can be divided into two types: one is the traditional tropospheric model based on early radio sounding observations, such as the Saastamoinen model, Hopfield model, and Black model, etc.…”
Section: Introductionmentioning
confidence: 99%